Development of Canva Application-Based Technology in Al-Qur'an Hadith Learning for Class X at MA Ma'arif 06 Seputih Raman - Alfani, Ajeng Khori; Q, Ikhwan Aziz; Wijaya, Adi (International Journal on Advanced Science, Education, and Religion, 2024)
The background of this development research is the lack of use of learning media in the classroom, making students bored in following the lesson. There are no teachers who develop technology during teaching and learning activities, one of which is the use of the Canva application. Canva is one of the online design programs that offers various sophisticated features in creating learning media, one of which is. Even an account for Canva Education specifically for students and educators is available. Currently, we need to realize the importance of technology for the nation's future generations and they are Gen Z who may still be in school. The purpose of this study is to develop technology based on the Canva application in learning the Al Qur'an Hadith for class X at MA Ma'arif 06 Seputih Raman. This study uses the Research and Development (RND) method and chooses one of the RND models, namely ADDIE. As the name implies, ADDIE goes through several stages of analysis, design, development, implementation and evaluation. Based on the research that has been carried out, a conclusion has been drawn, namely that this video-based learning media is suitable for use as a learning medium in the Al Qur'an Hadith subject for class X. The results of the media and material validation questionnaire showed results in the very feasible category. From the learning results using the pretest posttest, the average difference in value was 33.46. From the average pretest value of 51.81 and the posttest value was 85.27. So it is concluded that video learning media based on the Canva application is worthy of being developed.